SOCIO-ECONOMIC REFORMS IN LINE WITH THE MAQĀSID AL-SHARĪʿAH : THE CASE OF CALIPH ʿUMAR IBN ʿABD AL-ʿAZĪZ - Tahir, Ibrahim Nuhu (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2016)
The paper addresses the practical approach of the rightly-guided caliph, ʿUmar ibn ʿAbd Al-ʿAzīz. Its emphasis is on the unique and successful methods used by this exceptional leader. He led the Muslim community with justice and this in itself helped regain the prestige of the Muslims. The reforms he employed helped the society achieve not only one maqāṣid, but many maqāṣid. How did he manage to eradicate poverty to the extent that no Muslim needed charity during his reign? Success lies in re-tracing the footsteps of those who was regard as role models that provide a better example for later generations to emulate. What could possibly have the power to rejuvenate a failing society such as ours other than the realization of the awareness of Allah the All-Mighty over everything? Thus the paper will suggest some practical utilization of those indicated methods above that the government in our current society can emulate in order to ensure a better future for human socio-economic development. The main bases of this research are the historical facts and data addressing the current situation of the Muslim community.